Assessing feasibility and acceptability of a brief intervention for risky alcohol consumption in sexual health clinic attendees: a randomised controlled trial. Issue 2 (10th August 2015) - Roderick, Paul; S Sundaram, Sangeetha; Dimitrov, Borislav D; Dewhirst, Susan; Tucker, Linda J; Leydon, Geraldine; Sheron, Nick; Frater, Alison; Harindra, Veerakathy
Abstract : Objectives: To assess the feasibility and acceptability of screening attendees at a sexual health clinic (SHC) for alcohol misuse, and delivering a brief intervention (BI). To explore the effect of this BI on drinking and sexual behaviour. Methods: A consecutive sample of consenting SHC attendees aged ≥16 years were screened using Alcohol Use Disorders Identification Test Consumption (AUDIT-C). Men scoring ≥5 and women scoring ≥4 were invited to complete the full AUDIT, alcohol diary and baseline questionnaire. Interventions: Participants were randomised to receive BI by a trained sexual health professional or a standard alcohol leaflet (usual care, UC). All were followed up for changes in alcohol and sexual behaviour at 6 weeks and 6 months. A fidelity check and staff focus group were undertaken. Results: Of 664 participants screened, 215 (32%) were eligible for randomisation and 207 were included in the final analysis: 103 (BI) and 104 (UC). Follow-up rates were 54% and 47% at 6 weeks and 6 months, respectively. Both groups reduced alcohol consumption though the degree of change did not differ between them. There was some evidence of positive changes in sexual health risk in both groups. BI was delivered as intended, adding 5 minutes to the consultation, and staff feedback was positive. Conclusions: Alcohol misuse was common in SHC attendees. Systematic assessment and BI for alcohol misuse was feasible and acceptable to staff and patients. Identification and provision of standard information alone appeared to influence drinking and sexual behaviour. Trial registration number: ISRCTN19452424.